ANALISIS PENGARUH E-SERVICE QUALITY, HARGA DAN PROMOSI TERHADAP KEPUASAN PENGGUNA OVO MERCHANT PADA PELAKU UMKM DI DKI JAKARTA - Nur Khofivah, (2022)
The rapid development of technology and information has brought about changes in the payment system in Indonesia which can be accessed digitally through server-based Financial Technology. This study aims to determine the effect of e-service quality, price and promotion on the satisfaction of ovo merchant users on SMEs in DKI Jakarta. The sampling method used is purposive sampling, with a sample size of 100 respondents. In collecting respondent data using google form. This research uses Smart PLS 3.3 (Partial Least Square) software for analysis tools. The results of the analysis show that: (1) e-service quality has a positive and significant effect on the satisfaction of ovo merchant users on MSME actors in DKI Jakarta, (2) price has a positive and significant influence on ovo merchant user satisfaction on MSME players in DKI Jakarta. Jakarta and (3) promotion has a positive and significant influence on the satisfaction of ovo merchant users on MSME actors in DKI Jakarta.